2022
DOI: 10.31557/apjcp.2022.23.6.2001
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Apolipoprotein A1 (ApoA1) for Detecting Liver Cirrhosis and Hepatocellular Carcinoma

Abstract: Objective: Liver cirrhosis and hepatocellular carcinoma (HCC) are chronic liver diseases that can cause serious health problems. Meanwhile, the methods used to detect liver cirrhosis and HCC are limited. Apolipoprotein A1 (ApoA1) is a protein that makes up high-density lipoprotein (HDL), which plays a role in liver cirrhosis and HCC, and can be used as a biomarker. This study aims to determine the ability of ApoA1 to detect and differentiate liver cirrhosis and hepatocellular carcinoma. Methods: This cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…The high rate of hepatitis B infection in Southeast Asia and its accompanying comorbidities and consequences can be blamed for the high burden of HCC in HBV cases there. The results of this study agree with those of earlier studies [77][78][79][80].…”
Section: Discussionsupporting
confidence: 93%
“…The high rate of hepatitis B infection in Southeast Asia and its accompanying comorbidities and consequences can be blamed for the high burden of HCC in HBV cases there. The results of this study agree with those of earlier studies [77][78][79][80].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that elevated levels of APOA1 are associated with liver injury (Gumilas et al, 2022). In the present study, APOA1 was not only most highly expressed in the APOA1 + HCC subpopulation, but was also highly expressed in other malignant HCC cells; therefore, it may be a potential biomarker for HCC.…”
Section: Discussionsupporting
confidence: 58%
“…The deficiency or reduction of APOA1 can result in the accumulation of cholesterol in tissues, and cancer cells often show increased cholesterol synthesis, possibly due to the high cellular demand for cholesterol to support rapid proliferation and cell membrane synthesis, thereby promoting tumor growth. Gumilas et al ( 29 ) highlighted the potential mechanistic role of APOA1 in liver cirrhosis and hepatocellular carcinoma (HCC), stating that the primary biological function of APOA1 is to facilitate reverse cholesterol transport, transporting excess cholesterol from peripheral tissues to the liver for metabolism. Additionally, APOA1 possesses various biological properties such as anti-inflammatory, antioxidant, and immune-modulatory effects.…”
Section: Discussionmentioning
confidence: 99%